Coercion and HIV self-testing in Chinese men who have sex with men: implementation data from a cross-sectional survey. (December 2017) - Ong, Jason J; Li, Haochu; Dan, Wu; Fu, Hongyun; Liu, Ewen; Ma, Wei; Kang, Demin; Liao, Meizhen; Marley, Gifty; Wei, Chongyi; Tang, Weiming; Pan, Stephen; et al.
Abstract: Background: The wide range of interventions to promote HIV testing might inadvertently contribute to coerced testing. There has been concern about coerced HIV self-testing in non-research settings where there is minimal supervision. The aim of this study was to examine the prevalence and correlates of coerced HIV testing among men who have sex with men (MSM) in China. Methods: In July 2016, we recruited MSM from eight cities through BlueD, a gay social network mobile application. Data on sociodemographics, HIV self-testing, HIV facility testing, test coercion, condomless sex in the past 3 months, and transactional sex were collected. Coerced testing was defined as someone (partner, friend, employer, or others) forcing the participant to take an HIV test. Multivariable logistic regression was used to examine correlates of coerced testing among MSM who had ever received HIV testing. Findings: 1312 men were included, most of whom were young (mean age 26·9 years [SD 6·3]). 1002 (76%) men were identified as gay, and 685 (52%) men had used HIV self-testing. 64 (15%) men reported coerced testing, and 39 of these men were forced to have a self-test. Adjusting for age, education, income, and residence, men who reported coerced testing were more likely to have ever self-tested for HIV (adjusted odds ratio 4·25; 95% CI 2·23–8·09). Coerced testing was more common among men who had sex with casual partners in exchange for gifts or money (3·34; 1·90–5·86) than among men who did not report transactional sex. Coerced testing was also more common among MSM who reported condomless anal sex in the preceding 3 months (2·38; 1·43–3·98) than among men who did not report condomless anal sex. Interpretation: HIV test coercion is uncommon among MSM in China, but is more likely in men who used HIV self-tests. As HIV self-testing is scaled up worldwide, research and enhanced post-test surveillance are needed. Funding: National Institute of Allergy and Infectious Diseases (1R01AI114310-01) and the Australian National Health Medical Research Council (APP1104781). The funders had no role in the design of the study, the collection, analysis, and interpretation of data, or in the writing of the Abstract.